Global politics issues and perspectives - Kumar, Kamal; Jindal, Nirmal 1958- (SAGE Publications, 2018)
"Global Politics: Issues and Perspectives critically examines the issues and agencies of global governance from the third world perspective. Drawing upon the theoretical aspects and emerging global trends, the authors analyse the concept of globalisation in all its manifestations, including the role of social movements, transnational actors (IMF, WTO and OECD) and NGO networks. Written as per the latest UGC guidelines and supported by informative and insightful illustrations, this book will be an invaluable resource to the UG and PG students of Political Science and International Relations as well as UGC-NET and civil services aspirants. Covering a wide range of current topics such as nuclear weapons proliferation, global terrorism, environmental politics, human security and poverty, this book will enable students to understand the key developments in global politics and analyse contemporary events and pressing concerns of the twenty-first century through a neutral lens"--